Determination and Mapping of Regional Change of Pb and Cr Pollution in Ankara City Center - Cetin, Mehmet; Aljama, Akram Mohamed Omar; Alrabiti, Osama B. Muragaa; Adiguzel, Fatih; Sevik, Hakan; Zeren Cetin, Ilknur (Springer Science and Business Media LLC, 2022)
As in the whole world, environmental problems have increased with the increase in residential areas in Turkey, and this situation has brought many problems, especially environmental pollution. Among the components of environmental pollution, heavy metals are the most dangerous and important in terms of human and environmental health. Especially Pb and Cr are among the most toxic and deadly heavy metals, and the concentrations of these heavy metals in the environment are constantly increasing. Soil is one of the elements most affected by the increase in pollution. Soils are both a nutrition and living environment for plants and one of the most important components of the environment. In addition, topsoil is one of the most important indicators of the level of air pollution. This study aimed to determine and map the Pb and Cr pollution in the city center of Ankara, the capital and the second-largest city of Turkey, with the help of topsoils. Within the scope of the study, Ankara city center was divided into sub-regions with different characteristics, and Pb and Cr analyzes were performed by taking topsoil samples from 50 points representing these regions. Then, the changes in Pb and Cr concentrations on a regional basis were statistically evaluated, the data were transferred to Geographic Information Systems (GIS) using ArcGIS 10.7 software, then modeled with the kriging method, one of the interpolation methods, and pollution maps were created. As a result of the study, it has been determined that the Cr concentration is generally higher in the northwest-southeast axis of the study area, decreases as one goes to the northeast and southwest, and the region with the highest Pb concentration is located in the center of the study area, that is, in the west of the town of Sincan. Institute of Science Graduate Studies Research Projects; Kastamonu University Institute of Science Department of Material Science and Engineering This study was produced from a doctoral study at Kastamonu University, Institute of Science Graduate Studies Research Projects (Ph.D.). Thank you to advisor and Kastamonu University Institute of Science Department of Material Science and Engineering for Ph.D. thesis.
Keywords: Heavy Metal; Soil; Ankara; Pollution; Cr; Pb; 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water